2015
DOI: 10.3791/52637
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Rat Ischemic Skin Wound Model

Abstract: The propensity for chronic wounds in humans increases with ageing, disease conditions such as diabetes and impaired cardiovascular function, and unrelieved pressure due to immobility. Animal models have been developed that attempt to mimic these conditions for the purpose of furthering our understanding of the complexity of chronic wounds. The model described herein is a rat ischemic skin flap model that permits a prolonged reduction of blood flow resulting in wounds that become ischemic and resemble a chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Skin flaps are one of the classic approaches to induce ischemia. There are various types of flap models used for ischemic wound research: U shape peninsular incision with 2:1 length-to-width ratio, which can cause nearly 40% massive necrosis of the flap [ 40 ]; double pedicle ischemic model on white pigs and rats, which have a length-to-width ratio of 1.5:1, exhibited a severe ischemic state [ 41 ]. Utilizing our type 2 diabetic animal model and taking examples from the aforementioned references, we created a double pedicle flap to induce a relative ischemic condition for the wound healing study.…”
Section: Discussionmentioning
confidence: 99%
“…Skin flaps are one of the classic approaches to induce ischemia. There are various types of flap models used for ischemic wound research: U shape peninsular incision with 2:1 length-to-width ratio, which can cause nearly 40% massive necrosis of the flap [ 40 ]; double pedicle ischemic model on white pigs and rats, which have a length-to-width ratio of 1.5:1, exhibited a severe ischemic state [ 41 ]. Utilizing our type 2 diabetic animal model and taking examples from the aforementioned references, we created a double pedicle flap to induce a relative ischemic condition for the wound healing study.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the effects in wound healing between the various different wound dressing samples when applied to a bacterial infected skin wound on Sprague‐Dawley rats. It was reported that the rat species often employed to provide a suitable skin area for incisional and excisional wounding and tissue collection . It was taken into careful consideration that the skin of a rat and a human are different anatomically.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the bipedicle skin flap is an established model of ischemia [51][52][53] . In the current experiment, for the first time, we initially created a bipedicle skin flap on the back of each rat followed by an excisional wound in the flap.…”
Section: Scientific Reports |mentioning
confidence: 99%